THE YIELD LEVEL OF SHARIA FINANCING AND RELEVANCE TO THE PROFITABILITY PERFORMANCE OF BANK PEREKONOMIAN RAKYAT SYARIAH IN INDONESIA - Jhody Wiraputra; Ahmad Habibi; Muhammad Iqbal Fasa (Jurnal Dinamika Ekonomi Syariah, 2026)
This study aims to analyze the effect of Mudharabah financing, Musharakah financing, Murabahah financing, and Istishna financing on the profitability of SRB in Indonesia. This type of research uses a quantitative approach. The population of this study is all SRBs in Indonesia registered with the Financial Services Authority (OJK), as many as 173 SRBs. Meanwhile, the samples used in this study were 173 SRBs. The sample selection was based on a sampling technique, namely purposive sampling with two criteria, namely SRB registered with the Financial Services Authority starting from 2020-2024, and SRB that published its financial statements starting from 2020-2024. The results showed that the yield rate of Musharakah and Istishna had a negative and significant effect on the profitability of SRB. In contrast, Mudharabah and Murabahah yield levels showed no significant effect on SRB profitability. And simultaneously, variable yield Mudharabah, Musharakah, Murabahah, and Istishna affect the profitability of the Islamic People's Financing Bank (BPRS) in Indonesia.